Phytoremediation of the endocrine disruptors bisphenol A, linuron and 17α-ethinylestradiol in NOM-enriched water and freshwaters - Gattullo, C. E.; Cunha, B. B. [UNESP]; Loffredo, E.; Rosa, A. H. [UNESP]; Senesi, N. (Springer Nature, 2013)
The rising presence of endocrine disruptors (EDs) in the environment, especially in aquatic systems, may endanger wildlife and humans. The removal of EDs from water by means of the new and sustainable technology of phytoremediation appears promising, although more information is required about the feasibility to apply this technique to real polluted media. In this study, radish was tested during germination for its ability to remove the EDs bisphenol A, linuron and 17α-ethinylestradiol from four different media: distilled water, natural organic matter (NOM)-enriched water and two freshwaters collected in Southern Italy. In water, seedlings were only slightly affected by the mixture of EDs, and they removed a great amount of each ED. In the other three media, although the germination was generally inhibited, the removal efficiency of radish for all EDs remained high. Results of this study reveal the phytoremediation capacity of laboratory-prepared and actual aquatic systems for various EDs by radish.
Keywords: Endocrine disruptor; Freshwater; Germination; Natural organic matter; Phytoremediation; Radish